The influence of servant leadership on job performance: Role employee engagement mediation - Werdi Santoso; Siti Nur Azizah (International Journal of Applied Finance and Business Studies, 2025)
This study aims to explore the influence of servant leadership on job performance, with employee engagement as a mediating variable, on village officials in Pituruh District, Purworejo Regency. Using a quantitative approach, data were obtained from 120 respondents through questionnaires and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Square with the help of SmartPLS 4.0 software. The results of the study indicate that servant leadership has a positive and significant effect on employee engagement, with a coefficient of 0.667, and that employee engagement has a very positive effect on job performance, with a coefficient of 0.816. However, the direct relationship of servant leadership to job performance is not significant, with a value of -0.121. Therefore, it is proven that employee engagement fully mediates the effect of servant leadership on job performance. The R-square value for employee engagement of 0.445 and job performance of 0.549 indicates that the model has sufficient explanatory power. These findings indicate that in the context of public organizations such as village governments, servant leadership does not directly improve performance, but rather through increased employee engagement. Therefore, developing a service-focused leadership style and strategies to increase employee engagement is important in efforts to improve the performance of village officials.